Faces of joblessness in Portugal. A people-centred perspective on employment barriers and policies - Düll, Nicola; Thévenot, Céline; Immervoll, Herwig; Browne, James; Fernandez, Rodrigo; Neumann, Dirk; Pacifico, Daniele (Paris, 2018)
"In the aftermath of the financial and economic crisis, large shares of working-age individuals in Portugal either did not work or only to a limited extent. As the employment rate bottomed out in 2013, 29% were without employment during the entire year, and a further 10% had weak labour-market attachment, working only a fraction of the year, or on restricted working hours. This paper applies a novel method for measuring and visualising employment barriers of individuals with no or weak labour-market attachment, using household micro-data. It first develops indicators to quantify employment obstacles under three broad headings: (i) work-related capabilities, (ii) incentives, and (iii) employment opportunities. It then uses these indicators in conjunction with a statistical clustering approach to identify unobserved (“latent”) groups of individuals facing similar combinations of barriers. The resulting typology of labour-market difficulties provides insights on the most pressing policy priorities in supporting different groups into employment. A detailed policy discussion illustrates how these empirical results can inform people-centred assessments of existing labour-market integration measures and of key challenges across different policy areas and institutions. The most common employment obstacles in Portugal were low education/skills, a lack of recent work experience, scarce job opportunities and health problems. Financial disincentives and care responsibilities were less widespread overall, although important barriers for some groups. A striking finding is that 45% of jobless or low-intensity workers face three or more simultaneous barriers, highlighting the limits of narrow policy approaches that focus on subsets of these employment obstacles in isolation."